2014
DOI: 10.2217/pgs.14.97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymorphisms within Methotrexate Pathway Genes on Methotrexate Toxicity and Plasma Levels in Adults with Hematological Malignancies

Abstract: Our results in Asian adults provides evidence for the contribution pharmacogenetics to the toxicity of high-dose MTX and plasma MTX concentrations at 48 h following treatment in patients with acute lymphoblastic leukemia or non-Hodgkin lymphoma. These results will contribute towards the effort of MTX therapy individualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 60 publications
6
44
0
4
Order By: Relevance
“…70 . Some other authors confirmed the above analysis in recent studies [45,75]. In contrast with above results, some other authors did not find any association between MTHFR and MTX-related toxicity or other side effects [22,26,27,31,35,73,76].…”
Section: Methylenetetrahydrofolate Reductasesupporting
confidence: 57%
See 1 more Smart Citation
“…70 . Some other authors confirmed the above analysis in recent studies [45,75]. In contrast with above results, some other authors did not find any association between MTHFR and MTX-related toxicity or other side effects [22,26,27,31,35,73,76].…”
Section: Methylenetetrahydrofolate Reductasesupporting
confidence: 57%
“…In contrast, the CA genotype in A934C was associated with increasing risk of thrombocytopenia (grade 3/4, P=0.01). Suthandiram et al [45] …”
Section: Solute Carrier Organic Anion Transporter Genesmentioning
confidence: 99%
“…As an antifolate chemotherapeutic agent, MTX has been widely used in the treatment of adults with hematological malignancy, such as ALL, Burkitt lymphoma (BL), lymphoblastic lymphoma, non-Hodgkin's lymphoma (NHL), peripheral T-cell lymphoma (PTCL) and primary central nervous system lymphoma (PCNSL) [9,[11][12][13][14][15]. Although MTHFR genetic polymorphism have been implicated in MTX-induced toxicities in adults with breast cancer [16] and rheumatoid arthritis [17], as for adults with hematological malignancy, the results of relevant studies remain inconsistent and even conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Avivi et al found that MTHFR C677T or A1298C polymorphism had no impact on liver and kidney toxicities following MTX therapy in adults with adult non-Hodgkin's lymphoma [8]. On the contrary, Suthandiram et al revealed that MTHFR 677TT were associated with increased risk of both hematopoietic and hepatic toxicities in adults with hematological malignancies [9]. Considering the different study designs and insufficient power of individual studies, we performed a meta-analysis to combine available data to assess the possible associations between common MTHFR gene polymorphisms (C677T and A1298C) and MTX-induced toxicities in adults with hematological malignancy.…”
mentioning
confidence: 99%
“…Suthandriam et al [30] reported that patients with MDR1 C3435T polymorphisms appear to have significantly higher methotrexate (MTX) plasma concentrations in ALL or NHL patients. Min et al [31] showed that MDR1 G2677T/A gene polymorphisms, as well as haplotypes derived from C1236T, G2677T/A, and C3435T, were associated with individual differences of glucocorticoid treatment in idiopathic thrombocytopenic purpura.…”
Section: Association Between Mdr1 and Survivalmentioning
confidence: 99%